107k views
10 votes
Question 3 of 10

Subtract these polynomials.
(3x²+2x+4) - (x² + 2x + 1) =
A. 2x² + 5
OB. 2x² + 4x + 3
O C. 2x+3

User Joe Essey
by
6.0k points

2 Answers

2 votes

Answer:

answer is 2x^2 + 3

Step-by-step explanation:

3x^2 - x^2 is 2x^2

2x-2x is 0

4-1 is 3

User Divyanshu Rawat
by
6.0k points
5 votes

Answer:


\large \boxed{\sf 2x^2 + 3}

Step-by-step explanation:


\sf \Rightarrow (3x^2 + 2x + 4) -(x^2 + 2x + 1)

open the parenthesis


\sf \Rightarrow 3x^2 + 2x + 4 -x^2 - 2x -1

regroup variables


\sf \Rightarrow 3x^2 -x^2 + 2x - 2x+ 4 -1

add/subtract variables


\sf \Rightarrow 2x^2 +3

User Loner Shushman
by
5.7k points